2019
DOI: 10.14390/jsshp.hrp2018-011
|View full text |Cite
|
Sign up to set email alerts
|

Development of new therapeutic agents for preterm birth by glycosaminoglycan chain remodeling of urinary trypsin inhibitor

Abstract: This study aimed to examine the effects of the glycosaminoglycan (GAG) chain in urinary trypsin inhibitor (UTI) on uterine cervical fibroblasts (UCFs) and to apply the findings to the development of more effective therapeutic drugs for the management of preterm birth. Methods: We prepared GAG chain-remodeled UTIs by hydrolysis and /or transglycosylation by testicular hyaluronidase. These UTIs were added to UCFs obtained from gynecology operations, and the effects of UTIs on the release of IL-8, IL-6, MMP-8, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, we remodeled the GAG chain of UTI from low sulfated Ch4S to hyaluronan (HA), with no changes to the core protein to create the HA hybrid UTI (HA-UTI) as a tool for investigating native GAG chain functions as well as the possible superiority of HA-UTIs over native UTI. 13) 14) In the present study, we investigated the effect of the GAG chain on the activities of trypsin, chymotrypsin, plasmin, and pancreatic elastase. It was demonstrated that UTI having a native GAG chain showed stronger inhibitory activity on these proteases compared with HA-UTI or with UTI with only a linkage region as sugar chain moiety.…”
mentioning
confidence: 99%
“…Recently, we remodeled the GAG chain of UTI from low sulfated Ch4S to hyaluronan (HA), with no changes to the core protein to create the HA hybrid UTI (HA-UTI) as a tool for investigating native GAG chain functions as well as the possible superiority of HA-UTIs over native UTI. 13) 14) In the present study, we investigated the effect of the GAG chain on the activities of trypsin, chymotrypsin, plasmin, and pancreatic elastase. It was demonstrated that UTI having a native GAG chain showed stronger inhibitory activity on these proteases compared with HA-UTI or with UTI with only a linkage region as sugar chain moiety.…”
mentioning
confidence: 99%